Navigating hemodynamic turbulence in penetrating liver injury: a case report - Prayogo, Danniel Loogman; Sutrisna, Wayan Wahyu (International Journal of Advances in Medicine, 2025)
Penetrating liver injuries caused by knife wounds present significant challenges due to the potential for hemodynamic instability, which increases mortality risk. Early intervention and therapy for patients with hepatic trauma are crucial for effectively stabilizing the patient’s clinical condition. A 37-year-old male patient arrived at our emergency department (ED) presenting with clinical signs of Grade III hemorrhagic shock following a stab wound on the right upper abdominal quadrant. Initial stabilization in the ED included administration of 2000 ml of crystalloids while waiting for the blood products; however, the patient’s present transient response hemodynamic exchange. He was emergently taken to the operating room, and we conducted an exploratory laparotomy. Intraoperation revealed a Grade 4 liver injury, affecting liver segments number five and six with a laceration size of around 12 cm. Immediate surgical interventions included the Pringle maneuver and Hepatorrhaphy. The intraoperative blood loss was approximately 3000 cc, resulting in a postoperative hemoglobin level of 3 g/dl. During both the intraoperative and postoperative periods, the patient was receiving a total of 8 units of blood in 48 hours. The patient’s clinical condition improved significantly following all interventions. Patients with stab wounds, particularly those affecting the liver, face a significantly high mortality rate due to the potential for haemorrhagic shock. Immediate surgical intervention is crucial to controlling the bleeding in unstable hemodynamic patients. Additionally, blood transfusions play a vital role in stabilizing the patient’s clinical condition. Early management of patients with stab wounds with hemodynamic instability needs effective initial interventions and surgical procedures.